STRATEGY MARKETING FOR COMPETITIVENESS AGRO TOURISM WARAS FARM - CIKERAI ON CILEGON CITY - Sulaeni,; Setiawan, Johan; Miftah, Ajeng (Management Science Research Journal, 2023)
Waras Farm is a tourist spot that focuses on agriculture. Located in the Cikerai area of Cilegon City. The purpose of this research is to identify internal external factors and findalternative strategies and prioritize strategies to develop the business. The method used inthis research is descriptive qualitative. The analysis used in this research is internalexternal, IFE matrix, EFE matrix, IE matrix, SWOT matrix and QSPM matrix. Based onthe SWOT matrix, there are six alternative strategies that can be applied to Waras Farmagro-tourism, namely two SO strategies, one WO strategy, two ST strategies and one WTstrategy. The results of the IE matrix show that Waras Farm's agro-tourism is in quadrantV (growth strategy) with horizontal concentration by developing product and servicequality with the aim of avoiding lost sales and lost profits. From the results of the QSPMmatrix, the right alternative strategy to be applied to Waras Farm agro- tourism is to takeadvantage of natural conditions that have the potential to be used as agro- tourism with aback to nature trend.